Evaluation of pH Effect on Conformation of Protein Interaction E-Cadherin…ADTC5 Complex: Molecular Dynamic Simulation - Royhanshah, Moch Freskha Fauzi; Anam, Khairul; Hudiyanti, Dwi; Siahaan, Parsaoran (Universitas Diponegoro, 2023)
Abstract. Blood Brain Barrier (BBB) is a barrier located in the brain that controls the delivery of peptide drug to the brain. The difficulties of delivering drugs through BBB is because of E-Cadherin…E-Cadherin interaction that prevent drugs to pass through. ADTC5 has shown positive results to improve drug delivery through the BBB by modulating E-Cadherin…E-Cadherin interaction. Conformation are one of the factors that can affect the modulation stability between E-Cadherin…ADTC5. To analyze the conformation and stability of E-Cadherin…ADTC5 complex throughout the simulation time with pH effect, Molecular Dynamic (MD) method was used to simulate the conformational changes. The results indicate that pH 7.4, E-Cadherin…ADTC5 is the most stable conformation, with the lowest maximum radius gyration value 28.906 Å and the lowest ΔG Binding -168.244 kJ/mol. In the other hand, the most unstable conformation can be seen at pH 2.4, indicated by the positive ΔG Binding values 51,802 kJ/mol, high RMSD average at 2.8 Å and high RMSF fluctuations on residues.